O Pavão: - Fabio Dal Gallo; Cristina Alves de Macedo (Revista Brasileira de Estudos da Presença)
This article aims to discuss the creation of narratives in fire juggling spectacles, based on the case study of the work O Pavão (The Peacock). The importance of the limit variable of the logic of the risk of the instrument at the moments of conception, building and manipulating fire instruments and props is highlighted, so that the risk factors are controlled for the artists and the audience. As a result, it was identified that the circus spectacle, which featured juggling acts together with fire props, followed a line of tension and relaxation, building a narrative that dialogued with the theme of the event.